2015
DOI: 10.1175/jpo-d-14-0057.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixing, Dissipation Rate, and Their Overturn-Based Estimates in a Near-Bottom Turbulent Flow Driven by Internal Tides

Abstract: Direct numerical simulation (DNS) and large-eddy simulation (LES) are employed to study the mixing brought about by convective overturns in a stratified, oscillatory bottom layer underneath internal tides. The phasing of turbulence, the onset and breakdown of convective overturns, and the pathway to irreversible mixing are quantified. Mixing efficiency shows a systematic dependence on tidal phase, and during the breakdown of large convective overturns it is approximately 0.6, a value that is substantially larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…This is because convection is known for being a much more efficient mixing mechanism than shear-driven turbulence: for pure RayleighTaylor convection G ' 1 (Dalziel et al 2008;Gayen et al 2013). In other recent numerical work on large convective overturning events, that is, cases that have some resemblance to that presented here, Chalamalla and Sarkar (2015) found G 2 [0.67, 1], which is also close to the mixing efficiency of pure convection. For breaking waves such as those observed here, small-scale convectivelike structures occur because of potential energy anomalies (density inversions) created during the overturning motions.…”
Section: On Bore Formation Causing Buoyant Instabilitiessupporting
confidence: 81%
See 1 more Smart Citation
“…This is because convection is known for being a much more efficient mixing mechanism than shear-driven turbulence: for pure RayleighTaylor convection G ' 1 (Dalziel et al 2008;Gayen et al 2013). In other recent numerical work on large convective overturning events, that is, cases that have some resemblance to that presented here, Chalamalla and Sarkar (2015) found G 2 [0.67, 1], which is also close to the mixing efficiency of pure convection. For breaking waves such as those observed here, small-scale convectivelike structures occur because of potential energy anomalies (density inversions) created during the overturning motions.…”
Section: On Bore Formation Causing Buoyant Instabilitiessupporting
confidence: 81%
“…Very recently, the link between R OT and the evolution of turbulence was also explored for convective instabilities (Chalamalla and Sarkar 2015;Mater et al 2015). Again, the authors found larger R OT for younger turbulence (more potential energy) but also concluded that on average hR OT i ; O(1), where hi represent some carefully chosen ensemble average.…”
Section: Datamentioning
confidence: 99%
“…Additional campaigns tracking billows like those generated at IWISE L are needed to separate sampling biases from physically based biases that may exist. Such campaigns should also consider the influence that boundary length scales have on the scaling-an important physical bias in topographically influenced overturning not explicitly investigated here (see, e.g., Chalamalla and Sarkar 2015). Interestingly, and despite fewer profiles, the bias is not as apparent at the IWISE N2 site that shows excellent agreement in the lower 500 m-a finding we suggest may be related to strong bottom shear and local dissipation.…”
Section: Discussionmentioning
confidence: 76%
“…Higher mixing efficiencies occur in stratified flows with the presence of turbulent convection. Mixing efficiencies of 0.75 in the case of Rayleigh‐Taylor instability (Davies Wykes & Dalziel, ), 0.5 in the case of Rayleigh‐Bénard convection (Gayen, Hughes, & Griffiths, ; Hughes et al, ), 0.6 in the case of convectively driven instability due to internal waves (Chalamalla & Sarkar, ), and approaching 1 in the case of horizontal convection (Gayen, Griffiths, et al, ; Gayen et al, ; Vreugdenhil et al, ) have been found. In addition, the presence of rough topography could enhance mixing efficiency in the abyssal ocean (Mashayek et al, ).…”
Section: Introductionmentioning
confidence: 99%